(untitled) - PRIHATINI, LESTIANA (Language Horizon: Journal of Language Studies, 2014)
Peircian Triadic Semiotic Applied in Dan Brown’s The Lost Symbol Lestiana Prihatini English Literature Faculty of Languages and Arts State University of Surabaya retatsu_iena@ymail.com Dr. Ali Mustofa, M.Pd English Department Faculty of Languages and Arts State University of Surabaya Abstrak Dalam teks sastra tersusun oleh struktur. Sangat penting mengetahui struktur teks dalam sastra seperti plot, karakter, seting, nilai moral, penggunaan symbol- symbol yang membentuk teks. Hal yang sangat menarik sekali untuk mengetahui plot dan simbol- simbol dalam novel The Lost Symbol karya Dan Brown. Seperti yang kita ketahui, dalam novel ini bertebaran simbol- symbol. lebih menarik lagi jika teks ini dianalisis menggunakan triadik semiotik yang digagas oleh Peirce yang terdiri dari tiga elemen, yakni representamen, interpretant, dan objek. Beerdasarkan hal tersebut, menimbulkan pertanyaan, yakni (1) bagaimana triadik semiotik Peirce mendeskripsikan plot novel The Lost Symbol ? dan (2) bagaimana simbolisme mempengaruhi makna dalam tema novel The Lost Symbol ?. sebagai hasil dari penelitian, dalam plot novel tersebut tersusun oleh representamen, interpretan, dan objek. Selain itu, dalam novel ini terdapat empat symbol penting. The Hand Mystery mempunyai arti senagai undangan dan juga jembatan yang megubungkan karakter Robert Langdon dengan Mal’akh, air yang berarti penyucian diri, karakter Mal’akh yang mempunyai arti hasrat manusia dan Katherine Solomon yang merepresentasikan pengetahuan. Kata kunci: strukturalisme, triadik semiotik Peirce, representamen, interpretan, object, plot, simbol. Abstract In literary text, there must be built by certain structural stage. It is important to know the structural stage of the text like plot, characters, setting, moral value, the use of symbol which builds the text. In the Dan Brown’s The Lost Symbol, it is very interesting to know the plot and the use of the symbol of the story. Since we know that the story is complicated story which is adorned with thousand ancient symbol. It is more interesting if we analyze the plot and the symbol using Peircian triadic semiotic which consist of representament, interpretant, and object. Grounded on that presumptively facts, problems arise along with questionings, which are delivered to two main questions of (1) How does Peircian triadic semiotic describe the plot of The Lost Symbol novel? And (2) how does symbolism work in suggesting the meaning of theme in The Lost Symbol novel?. The result describes that representament, interpretant and object have role in describing the plot of the story. So, by using those three elements we can know the plot of the story. also, by using Peircian triadic semiotic, it can be found fours symbols which suggesting the theme in The Lost Symbol novel. Those are the hand mystery as the ‘bridge’ which relates Robert Langdon, Mal’akh and the journey to reveal the lost symbol, Katherine Solomon as the symbol of knowledge, water as the symbol of purity, and Mal’akh as the symbol of human desires. Keywords: structuralism, Peircian Triadic Semiotic, representament, interpretant, object, plot, symbols. INTRODUCTION All of texts in this world were built using literary elements. The elements were consisted of intrinsic and extrinsic element. Intrinsic element was consisted of characters, plot, setting, and tone elements. Extrinsic element was consisted of moral value, symbols and other elements. They had important role in shaping the story. It was just like The Lost Symbol novel written by Dan Brown. Those elements were decorating and shaping the story. It also decorated with symbols. All of the symbols were related to the enlightenment symbols. Since the theme of the story was about enlightenment, from the holes story were telling about the way people in searching enlightenment. Facing this condition, this research focused on the study of symbols which build the novel. As we know, “Symbol is one of literary work parts. It describes any expression feelings, ideas, emotions, by suggesting what these feeling, ideas and emotions are, by re- creating the feeling, ideas, and emotions in the mind of the reader through use of unexplained symbols” (Chadwick, 1971: 2). According to Chadwick symbol was part of literary work. It had function in describing expression of feelings, emotions and ideas by using several ways. First, symbol could be described by giving suggestion in order to find out the meaning of these feelings, emotions and ideas. Thus by giving the suggestion, the reader could get what the meaning of the symbol. Second, symbol could be described by re creating or re shaping the feelings, emotions and ideas in the reader’s mind to interpret symbol which cannot be explained easily. As the function of feeling and ideas expression, symbol had important role in knowing the identity of texts. By knowing the identity of the texts, so we could reveal the theme of the novel. By using symbolism theory, the researcher hopes can reveal the meaning symbols which related to the theme of the story. As we know that the theme of the story is enlightenment. In this research, it would also use semiotic approach. The semiotic approach that would be used is Peircian Triadic semiotic. In Peircian triadic semiotic was consisted three major elements of semiotic, those are representament, interpretant and object ( Kaelan, 2009: 195). Those three elements would be used in analyzing the plot of The Lost Symbol novel. For the researcher, Peircian semiotic triadic terminology was a fit approach in analyzing The Lost Symbol novel. As we know, in the The Lost Symbol novel consists of continuing plot and sometimes there were flash back which make the story stronger. Because of that matter, semiotic approach would be used in order to establish the formula of the story. The research would be focused on signing each plot by using semiotic approach. Hopefully, it would be curved a unity plot by using this approach. Thus by plotting the novel, we could know the sign of enlightenment which had built the story. Hopefully, by using both theories and concepts, the researcher will get the data. Nonetheless, based on facts lay on the background of the study above, then the problems are emerged and divided into two: 1. How does Peircian triadic terminology describe the plot of The Lost Symbol novel? 2. And how does symbolism work in suggesting the meaning of theme in The Lost Symbol novel? As referred to the background and statement of the problems above, this study has purpose to describe the plots and symbols in Dan Brown’s The Lost Symbol by using symbolism and semiotic approach. Also, by studying the novel, it can be used as literature for the next study or research. In accordance, by doing the research, this proposal can to be additional reference to make another research related to semiotic approach. Besides that, we can describe the meaning of signs in the novel. Additionally, in practical significance, this study is obtained can contribute to the practice of analyzing literary works by applying proper literary concept and theory. Hopefully, to whom this study may concern, it can be utilized as reference. Furthermore, this study expectantly can assist the institution to provide rich collection of research references. RESEARCH METHOD This study takes the data source from a novel entitled The Lost Symbol written by Dan Brown, published in London by Bantam Press, with ISBN 978-0-552-16123-7 in 2019. To collect the data, the first step is doing close reading the novel entirely. It is done over and over in order to be able to catch and understand the core story—intrinsically and extrinsically—of the novel. Besides, it also aims to support in collecting and analyzing the statement of the problems later on. Secondly, it comes to the step of collecting data. It is needed some methods to analyze the novel. Since the purpose of the study is to uncover the symbol of The Lost Symbol novel, so the study will analyze the novel using semiotic and symbolism approach. First of all, the research will use semiotic approach to identify the signs in the novel. By knowing the signs of the novel, so the researcher will know the plot of the novel. After knowing the plot, the symbol of the novel will be known and it will be analyzed. Theory of Symbol Symbolism is literary devices which used by writer in order to add meaning of their writing. Symbolis m itself is something which is stand to something else. Based on The American Heritage Dictionary of English Language 3rd edition, the word symbol means something that represents something else by association, resemblance, or convention, especially a material object used to represent something invisible. Is also has meaning as a printed or written sign used to represent an operation, an element, a quantity, a quality, or a relation of some matter. (Soukhanov:S7223) A symbol is anything which representing something else in a completely arbitrary relationship. There is no natural rule to represent something. In other words, the relation between signifier and signified depend on the observer. “Symbol is one of literary work parts. It describes any expression feelings, ideas, emotions, by suggesting what these feeling, ideas and emotions are, by re- creating the feeling, ideas, and emotions in the mind of the reader through use of unexplained symbols” (Chadwick, 1971: 2). In wider meaning, symbolism can be defined as art of expressing ideas and emotions by suggesting what these ideas and emotions are. In the novel or drama, symbolism is used for expressing the idealism of the novel. Thus, by symbolizing the novel, people can know the themes, emotions, ideas that build the novel. Without symbolism, there can be no literature. Symbolism has very important role in coloring literary works. Symbol, in this case, is included in the category of sign. In Peircian triadic terminology, sign consists of three categories, they are icon, index, and symbol. Those three aspects have important function in giving the meaning of the literary works. They will be explained in the semiotic theory. 2.2.2 Charles Sanders Peirce’s Semiotic theory Semiotic is the study of sign. The function of semiotic is analyzing the signs of many field, it can be art, architecture, language, and also literary works such as; poetry, short story, drama and so on. There is no limitation in studying the object. Basically, all of things in the world have sign. For example, a thing which made from wood, it has four legs and people usually use this kind if thing to sit, for Indonesian, they call it as KURSI, for England, they call it CHAIR and also many different country have their own language to call this thing. Here semiotic has contribution to interpret the thing. This is very simple example and there will be a lot of thing which need to interpret in order to make human know and understand how this kind of thing can be happened. First, semiotic was studied by Ferdinand De Saussure. His focus study is in the language. He introduced dyadic semiotic to identify the sign. He defines sign as signified and signifier. Something which is referring to the sign called signifier. In contrary, something which is referred to the sign called signifier. Both of the elements hare deep relationship in order to interpret the sign. The sign cannot be interpret if one of the elements does not exist. If Ferdinand de Saussure was the first person who introduced semiotic as the study of sign, there was another person has studied about semiotic. His name is Charles Sanders Peirce. He is one of the semiotic philosophers. He is an American philosopher. His sign has made him famous among philosophers in the world. Peirce sees sign as growing series sequenced. He has stated that the sign has influenced to somebody. One way with Saussure, deep relation between sign and somebody cannot be separated. In the way to interpret something, Peirce introduces three elements of sign. In this case, he calls those three elements as triadic model. According to him, sign is consisted with representatment, object and interpretant. Those three kinds of elemet have deep relationship in interpreting things. In his letter to Lady Welby (1904) in Critical Theory Since 1965 he stated that: “ I was long ago (1867) led, after only three or four years’ study. To throw all ideas into the three classes of firstness, secondness, and thirdness […] I call these three ideas the cenopythagorean” (Adams and Leroy:1986:639) From the letter peirce noted three kinds of signs, those are firstness, secondness and thirdness. Further, Peirce in (Adam and Leroy: 1986:639) explains the three aspects in more details. According to him, the firstness is a sign which is shaped as its own sign, it does not need reference or anything else. It can be interpreted by thought. Then, secondness is the mode of sign which has relationship with time and place out of it. It refers to the other which connected to something else. The last, thirdness is mode of sign which has relationship between secondness and thirdness. In this case, firstness is a representament, secondness is object, and thirdness is interpretant. Peirce in Chandler (2007: 29) noted that: “A sign … [in the form of a representament] is something which stands to somebody for something in some respect or capacity. It addresses somebody, that is, creates in the mind of that person an equivalent sign, or perhaps a more developed sign. That sign which it creates I call the interpretant of the first sign. The sign stands for something, its object. It stands for that object, not in all respects, but in reference to a sort idea, which I have sometimes called the ground of the representament.” From the quotation above can be explained as: the representament is the form which the sign takes. It is not limited in any material as long as the thing can be interpreted as representament. In this case, representament is a perception about something represent by object. an interpretant is about the sense to make the sign. an object is about something beyond the sign to which it refers. Later Peirce shows the form of triangle diagram bellow; representament interpretant object figure 1.1 Peirce’s triadic model ( Chandler, 2007: 30) To make signs more specific, Peirce classifies three basic semiotic elements, those are, sign or representatament consist of qualisign, sinsign, and legisign, object which consists of icon, index, and symbol, and the last is interpretant which consists of rheme, decisign, and argument. Those classifications will be explained more bellow: 1. Sign (Representament) As Peirce said in previous explanation that sign or representament is something which can be interpreted into something. On this semiotic element, Peirce explains more about the classification of signs which are mentioned bellow: A qualisign is everything that has quality to be sign. It cannot be functioned as a sign until it is shaped as sign (Zaimar, 2008:5). Everything which can be a sign called qualisign. Peirce stated that qualisign can be assign if the qualisign get a shape or embodied (Peirce in Zoest 1993:19). For example, red can be qualisign as love, but it can be embodied as sign if it has shaped itself. Sinsign is an individual object or event. It is the replica of legisign Legisign is the nature of a general type. It is a sign which consist a general idea, a norm or a low. It has definite identity. 2. Object The next division of sign is about sign related to their dynamic object. Here, peirce is also divided the relation of sign and object into three classification, those are; Icon In his letter to Lady Welby, Peirce ( Hazard,1986:634) defines icon as sign which determined by its dynamic object by virtue of its own internal nature. In this case, icon is defined as sign which similar to its object. The thing in this context must not an exact thing, it can be the imitation or just the playing of mind about something. From the semiotic triadic, Peirce makes three iconic sub classification, those are typology iconic, diagrammatic iconic and metaphoric metabolism. Zaimar (2008, 5) explains about the three iconic sub classification, those are; Iconic Typology is about relation between two things which is have resembled in shape, for example map, realist picture. diagrammatic iconic is about the relationship which is has resembled in step, like in diagram. Metaphorical iconic is a relationship between two different things that have likenesses. For example, it is about girl and rose. They have resembled in beauty and freshness, but the resembled is not total resembled. Index or indexical Index is assign mode in which the signifier is not arbitrary, but it is physically or causally connected to the signified. The connection can be observed with natural signs, medical symptoms, measuring instruments, pointing, personal’s works, etc. indexical is characterized by contiguity or relation. Elizabeth Bruss (1978:88) notes that the most important characteristic of indexical is relationship rather than quality. It just only needs demonstrable connections to something else. According to her, the most important connections are spatial co- occurrence, temporal sequence, and cause and effect. Similar with Bruss, Zaimar (2008: 5) also argues that index is relationship which has existential scope. He explains that existential means something which existed because there is another thing that makes it exist or there is cause and effect. For example, there will be no smoke if there is no fire. Smoke can be represented as sign for fire existence and in this relationship smoke is an index. Symbol Symbol is kinds of sign mode in which the signifier is differ with the signified, but it is very arbitrary or conventional. Symbol is usually interpreted by using rule or habitual connection. It can be connected with object by using high idea symbols. For Peirce, a symbol is a sign which refers to the object that denotes by virtue of law, it usually consists of general ideas that makes the symbol can be interpreted as the referring object (Peirce, 1931: 58). 3. Interpretant Peirce also divided classification of sign based on its relation with interpretant. Peirce divides sign into three classes, those are; Argument Argument is a sign which is functioned as the conclusion of something. It can give reason about something. Whenever we come to understand a sign as focusing our attention upon some conventional feature of its relationship with object, that is enabling us to understand the sign as part of a rule governed system of knowledge and sign. Rheme The sign determines an interpretant by focusing our understanding of the sign upon the qualitative features. It employs in signifying its object, then the sign is classified as a rheme. Noth (2006: 45) argued that rheme belongs to sign that is not true or false. It is kind of qualitative probability sign which draws the object. It belongs to kinds of sign that the people can choose several choices from the object. Dicent Dicent is a sign which represent according to facts. As Peirce said in his letter (Adam, 1986: 644) dicent is kind of sign which represented in its signified interpretant in real relation to its object. Sign can be classified as dicent if there are several facts that support the object. STRUCTURAL ANALYSIS Robert Langdon Mal’akh The lost symbol Based on the Peircian Semiotic triadic above, it can be concluded that The Lost symbol novel has flashback plot which is arranged chronologically and there are flashback which fill in the background for full understanding of the present event in the story. The story is arranged from event which has big influence in arranging the story, then followed by conflict that has meaning as “ the gate of journey” of the story, then followed by flashback about the past experience of the antagonist character. In this case, the antagonist character has role as the main character of the novel. After that the conflict is increasing to the climax of the story and it is ended with final situation or resolution. The story of the novel is separated into eight major plot sequences. Each sequence is describing about the story start from the beginning to the end of the story. By using Peircian triadic semiotic, the writer can explore the plot of the story. The writer finds the formula of the story. The plots explanation can be seen below. The first plot is explaining about initiation ceremony which is held by Masonic brotherhood. Asking for Mal’akh to pronouncing faithful agreement in front of the other Masonic members is the representament of the plot. Receiving the agreement by Masonic member from Mal’akh is the interpretant. The confession that Mal’akh is the new member of the highest degree in Masonic brotherhood is the object o the story. The second plot that has used peircian triadic semiotic explains about Robert Langdon who summons by Mal’akh in order to reveal the Lost Symbol. From the plot explanation that has explained above, Robert Langdon has role as the representament of the story. In this case, Robert is called as the representament because the character Robert Langdon has capability in revealing the Lost Symbol. Mal’akh as the interpretant knows that Robert has capability in revealing the Lost Symbol and he knows that Robert Langdon is the only man in the world who can unlock the mystery of the lost symbol. The final object of the first plot of the novel is the Lost Symbol. The Lost symbol is the object of the story because this is the thing what Mal’akh’s want. Finding the lost symbol is the bridge for Mal’akh to fulfill what he is dreamed. The third plot is explaining about Robert Langdon who tries to reveal the meaning of the hand mystery. From the long explanation above, the hand mystery has role as the representament. Mal’akh’s willingness in revealing the lost symbol is the ground why the hand Mystery appears in the story. By using the hand mystery, Mal’akh wants to give a ‘greeting’ to Robert Langdon that langdong is the only man in the world who will unlock the mystery of the lost symbol for him. As the interpretant, Robert Langdon understands that the hand mystery has meaning as the invitation. In other word, Robert Langdon understands that the invitation is for him. Also, the invitation is the tool to summon Robert Langdon in revealing the lost symbol. Invitation is the object of the second sequence plot. Based on the Robert Langdon’s perception, the Hand mystery has meaning as invitation. As the object of the story, the hand of mystery also has meaning as the ‘bridge’ for Robert Langdon in revealing the lost symbol. The fourth plot is explaining about Mal’akh wants to kill Katherine Solomon. In this plot, Mal’akh has planning to kill Katherine Solomon. Destroying Solomon’s research laboratory is one of the reasons that make Mal’akh wants to kill Katherine Solomon. This situation indicates a representament. Another reason that indicates the representament of the plot is desire of revenge. There is flashback that tells about Solomon’s past experiences. Past experiences that has happened between Mal’akh and Peter Solomon’s family is also the representament why Mal’akh tries to kill Katherine Solomon. Katherine understanding about what Mal’akh has done is the interpretant. The fifth plot is explaining about Robert Langdon and Warren Bellamy trying to encode the chipper pyramid in order to find the further clue to reveal the lost symbol. The chipper of pyramid is the tool or the clue that is used to help Robert Langdon and Katherine Solomon to reveal the lost symbol. It indicates that the chipper of pyramid has role as the representament. On the other hand, Robert Langdon and Warren Bellamy are the people who try to understand and analyze the chipper of pyramid. in this case Robert Langdon and Warren Bellamy is the interpretant. By interpreting the chipper of pyramid, they can find further clue to reveal the lost symbol. As the result, from the chipper of pyramid appears sixteen jumbled letters. It indicates the object of what Robert Langdon and Warren Bellamy has interpreted. The sixth plot explanation is explaining about Robert Langdon and Katherine Solomon who try to rearrange the sixteen jumble letters into meaningful letters. In this plot, the sixteen jumble letters are the representament. This is the sign that must be interpreted by Robert Langdon and Katherine Solomon. On the other hand, Robert Langdon and Katherine Solomon as the interpretant must interpret the meaning of sixteen letters. Further, in this plot Robert Langdon and Katherine Solomon find symbol A.D 1514 from little box which has brought by Robert Langdon. This is another representament or sign to rearrange the sixteen letters. The symbol is pointing to a magic square that is painted in painting of famous painter, Albrecht D?rer’s Melencolia I. By using the magic square, Robert Langdon can arrange the sixteen letters that stands for One True God. It indicates the object of what Robert and Katherine look for. It also indicates the representament because from the object Robert Langdon and Katherine Solomon can find another clue. As the interpretant, Robert Langdon and Katherine Solomon interpret those icons in order to reveal the lost symbol. The result of what they have analyzed is another words which stands to certain place in Washington D.C. It indicates the object of the plot in this sequence. The seventh plot that has described using Peircian triadic semiotic is Mal’akh’s effort in interpreting the meaning of the words that has revealed by Robert Langdon and Katherine Solomon. Mal’akh’s effort in revealing the rest clue in the capstone is the representament. The background or the ground of this situation is by revealing the rest of clue, Mal’akh can held sacrifice ceremony. In this plot sequence, indicates the climax of the story. The sign that signaling the sequence calls the climax is Mal’akh’s confession about his real identity in front of Peter Solomon. Besides that, the fulfillment of Mal’akh’s desire is the representament that the plot is the climax of the story. The eight plot is indicates the resolution of the story. In this case, the fulfillment of Mal’akh’s desire to transform him into the greatest one is the resolution of the story. It also indicates the representament. Mal’akh’s vision about his complacency is the interpretant of sacrifice ceremony that he held. The final ending that Mal’akh misperception about what is the real meaning of the lost symbol that cause his death is the object of the plot sequence. SYMBOLS ANALYSIS In this part, the research will be focused on the symbols which related to the theme of the story. Since the themes of the story in this research is revenge, desires, purification, love and transformation, the symbols will be focused on the symbols which related to the themes of the story. The symbols will be analyzed using Peircian semiotic theory. 1 The Hand Mystery The first symbol that will be analyzed in the story is The Hand Mystery. The hand Mystery is the first sign which is given by Mal’akh in summoning Robert Langdon to reveal the lost symbol. In this research, the hand mystery will be analyzed based on the representament, interpretant and the object. As we know that the representament will be existed if there is ground which makes sense of the representament, the ground of The Hand Mystery as the symbol is Mal’akh’s desires to transform him to be the greatest one. The only way to get what he wants is by revealing the Secret ancient symbol or the Lost Symbol. in this case, Mal’akh cannot reveal the ancient secret symbol, so he uses The hand Mystery as the “ bridge ” to link him with Robert Langdon, the person who able to reveal the lost symbol. “ A wave of nausea rushed over him. Langdon inched closed, unable to breathe, seeing now that the tips of the index finger and thumb had been decorated with tiny tattoos. The tattoos, however, were not what held Langdon’s attention. His gaze moved instantly to the familiar golden ring on the fourth finger. ” (Brown, 2009: 69) Based on the quotation above, the hand mystery is drawn as a hand which is tattooed with tiny tattoos. The tattoos which are tattooed on fingers is a symbol. The symbol means invitation. Further, based on the relationship between ground and the representament is qualisign. Based on the quotation in “a crown….,and a star.Langdon crouched down, eyeing the tips of Peter’s thumb and little finger. tattoos?” (Brown, 2009: 80). The quotation above explains about the quality of the hand. In this case, there is a crown on the thumb and a star on the little finger. In this case, the hand mystery is a representament or sign which is interpreted as invitation. In the story, the hand mystery is the ‘bridge’ between Robert Langdon and Mal’akh in revealing the lost symbol. By using the hand mystery Mal’akh can summon Robert Langdon to reveal the lost symbol. Besides that, The hand mystery has important role in leading Robert Langdon in unlocking the mystery of the lost symbol. 2 Water The second symbol that emerges in the novel is water. Water is one of natural elements which has important role in human life. In this novel, water has metaphorical meaning as purification. “ Mal’akh stood naked in the billowing warmth of his steam shower. He felt pure again, having washed of the remaining scent of ethanol” ( Brown, 2009: 360-361). The quotation is indicating that water that is used by Mal’akh take a bath has meaning as purification. In this case, steam shower is the representament. It is called as the representament, because steam shower can stand to be something else. The steam shower itself has meaning as purification. This is the object. By taking a bath, Mal’akh feels pure again. There is no any stain which stucked and tainted smell in his body. 3 Mal’akh Mal’akh is the main character who has role as antagonist character. In this story, Mal’akh is representing human desires. In this case, Mal’akh is represented as human desire because has strong wish or willingness in doing something, that is changing him to be the greatest one. “ Zachary became Andros. Andros became Mal’akh. And tonight…Mal’akh will become his greatest incarnation at all.” (Brown, 2009: 590). The quotation is the representament that sign Mal’akh’s desire. It can be seen from his personal and identity alteration from Zachary, Andros, and Mal’akh. “The moment Zachary received the money, he broke from the family, disappearing from the house without taking any of his belongings. He surfaced a few months later in the tabloids: TRUST FUND PLAYBOY LIVING EUROPEAN HIGH LIFE. The tabloids took joy in documenting Zachary’s spoiled life of debauchery. The photo of wild parties on yachts and drunken disco stupors were hard for the solomons to take,” (Brown, 2009: 281). From the quotation above is explaining about Zachary personality before he changes into Mal’akh. The quotation explains how Zachary fulfill his desire which make him joy. This condition indicates the representament which is representing human desire. In this case, Zachary fulfills his desire with fund that has already given by his family. Another quotation that represents human desires is, “He chose a Greek name – Andros Dareios – Andros meaning ‘warrior’, and Dareios meaning ‘wealthy’.[…] he began life anew – exploring never-before-imagined pleasures. The serenity of sailing alone on the ink-blue Aegean Sea became his new heroin trance; the sensuality of sucking moist arni souvlakia right off the skewer became his new Ecstasy; and rush of cliff diving into the foam-filled ravines of Mykonos became his new cocaine” (Brown, 2009: 306) The quotation above is explaining about Zachary’s alteration personal identity. The quotation also explains about the way of life that is chosen by Zachary after he escaped from Turkey Prison. He fulfills his desires with enjoying the scenes of his new place. This situation indicates that the way of life that Andros has chosen has role as representament. It is representing human desires. Like a common human, when one desires has fulfilled will be emerged another desires which wants to be fulfilled. In other words, human is never satisfied with what have they reach. This situation also happens to Andros. “ and yet, incredibly, he felt as empty as he had in that Turkish prison. What is it I am missing?” (Brown, 2009: 307). This quotation indicates that Andros does not satisfy in what he has reached. This dissatisfaction point makes Andros tries to find the answer. “ it was not until Andros read John Milton’s Paradise Lost that he saw his destiny materialize before him. He read of the great fallen angel… the warrior demon who fought against the light…the valiant one…the angel called Moloch. Moloch walked the earth as a god. The angel’s name, Andros later learned, when translated to the ancient tongue, became Mal’akh. And so shall I.”(Brown, 2009: 388). The quotation above is the answer of Andros’ question. The quotation is the representament that represent Mal’akh desire. In this case, Mal’akh has desire to reveal his real identity. In this quotationtation there is an icon name Mal’akh which is related to Moloch. According to Cox (2009: 25), the name Mal’akh is adapted from a horrifying apostate angel named Moloch. Moloch is the name of God and the name of particular sacrifice in some culture in the Middle East, including Jewish, Egyptian, and Phoenician. Based on the myth, and the story, Mal’akh is described as very horrifying man. He kidnaps and cuts his father’s right hand for his own purpose. He uses his father’s right hand as the invitation for Robert Langdon in revealing the lost symbol. Not only that, in the past, he kills his grandmother just for asking the location of the lost symbol. Mal’akh also tries to kill his own aunty and burns her laboratory just for fulfills his desire. 4 Katherine Solomon Another symbol which is spread in the novel, there is character named Katherine Solomon. She is one of the woman characters in this novel. She accompanies Robert Langdon in revealing the Lost Symbol. In this term, Katherine Solomon is representing of knowledge. “ Despite her brother’s occasional prodding, and no shortage of suitors, Katherine had never married. Science had become her life partner, and her workhad proven more fulfilling and exciting than any man could ever hope to be. Katherine had no regret.”(Brown, 2009: 44) Her broad knowledge is one of the representament or sign that she is representing as knowledge. “ Katherine’s two books on noetics had established her as a leader in this obscure field, but her most recent discoveries, when published, promised to make Noetic Science a topic of mainstream conversation around the world.” (Brown, 2009: 44). The quotation above describes how capable Katherine Solomon is. The quotation also indicates the the representament that signaling Katherine Solomon is representing as knowledge. CONCLUSION From the hole explanation it can be concluded that by using the Peircian triadic semiotic, we can describes the plot of The Lost Symbol novel. Based on the explanation above there is ‘formula’ which build The Lost Symbol novel. The novel is arranged in chronological sequence and flashback sequence which has role to strong the story. The story of the novel is separated into eight major plot sequences. Each sequence is describing about the story start from the beginning to the end of the story. The story is arranged from event which has big influence in arranging the story, then followed by conflict that has meaning as “ the gate of journey” of the story, then followed by flashback about the past experience of the antagonist character. In this case, the antagonist character has role as the main character of the novel. After that the conflict is increasing to the climax of the story and it is ended with final situation or resolution. There are four symbols that suggest the theme of The Lost Symbol novel. In the story, there is icon of the hand mystery which has meaning as invitation. This is also has role as the ‘bridge’ for Robert Langdon to reveal the lost symbol which has summoned by Mal’akh. The second is the icon Mal’akh character which has meaning as human desire. In this story, Mal’akh is the sign or representation of unlimited desires which has by human. In other word, Mal’akh is the representations of human which have never satisfy with what they have got. Next, water is the symbol of purification. In this case, water is used by Mal’akh to purify himself from the smell of ethanol. Besides that, water is also has meaning as the purification of sin. The last is, the icon Katherine Solomon character is the representations of knowledge. In this term, Katherine’s capability, interest in noetic science signaling that she is the metaphor of knowledge which change human thought about knowledge. REFERENCES Adams, Hazard and Leroy Searle. Critical Theory Since 1965. Tallahassee: Florida State University. Asyhar, Hanif. 2005. The Symbolism in Herman Melville’s Moby Dick by using semiotic approach. -: Gajayana University Beebe, Maurice. 1968. Literary Symbolism. California: Wadswirth Publishing Company. Brown, Dan. 2009. The Lost Symbol. United Kingdom: Corgi Book. Chadwick, Charles. 1971. Symbolism. Great Britain: Cox and Wyman Ltd. Chandler, Daniel. 2002. Semiotic the Basic. New York: Routledge. Christomy, Tommy and Untung Yuwono. 2004. Cultural Semiotic. Depok: PPKLBLP Indonesia University. Kaelan. 2009. Filsafat Bahasa Semiotika dan Hermeneutika. Yogyakarta: Paradigma Mansyur, Maulana. 2010. A semiotic analysis on the novel “ The five People You meet in heaven”. Jakarta: journal Noth, Winfried. 2006. Semiotik. Surabaya: Airlangga University Press. Zaimar, Okke K.S. 2008. Semiotik dan Penerapannya dalam Karya Sastra. Jakarta: Pusat Bahasa Departemen Pendidikan Nasional.